2012
DOI: 10.5194/bg-9-907-2012
|View full text |Cite
|
Sign up to set email alerts
|

A model study of the seasonal and long–term North Atlantic surface <i>p</i>CO<sub>2</sub> variability

Abstract: Abstract. A coupled biogeochemical-physical ocean model is used to study the seasonal and long–term variations of surface pCO2 in the North Atlantic Ocean. The model agrees well with recent underway pCO2 observations from the Surface Ocean CO2 Atlas (SOCAT) in various locations in the North Atlantic. Some of the distinct seasonal cycles observed in different parts of the North Atlantic are well reproduced by the model. In most regions except the subpolar domain, recent observed trends in pCO2 and air–sea carbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 58 publications
0
42
0
Order By: Relevance
“…Also other studies support the temporary decrease of North Atlantic CO 2 uptake during several years of the past decade (Corbière et al, 2007;Schuster et al, 2009). These variations are at least partially attributed to oceanic variability in the North Atlantic associated with a surface pressure pattern change known as North Atlantic Oscillation (Wetzel et al, 2005;Thomas et al, 2008;Tjiputra et al, 2012). In a model study with six coupled Earth system models, Keller et al (2012) identified a see-saw pattern of variations in sea surface pCO 2 between the North Atlantic subtropical gyre and the subpolar Northern Atlantic with an amplitude of ±8 ppm.…”
Section: Detection Of Ongoing Ocean Carbon Sink Strength Variabilitymentioning
confidence: 99%
“…Also other studies support the temporary decrease of North Atlantic CO 2 uptake during several years of the past decade (Corbière et al, 2007;Schuster et al, 2009). These variations are at least partially attributed to oceanic variability in the North Atlantic associated with a surface pressure pattern change known as North Atlantic Oscillation (Wetzel et al, 2005;Thomas et al, 2008;Tjiputra et al, 2012). In a model study with six coupled Earth system models, Keller et al (2012) identified a see-saw pattern of variations in sea surface pCO 2 between the North Atlantic subtropical gyre and the subpolar Northern Atlantic with an amplitude of ±8 ppm.…”
Section: Detection Of Ongoing Ocean Carbon Sink Strength Variabilitymentioning
confidence: 99%
“…For example, using ocean biogeochemical general circulation models, Thomas et al (2008), Tjiputra et al (2012), and Keller et al (2012) show that over interannual time scales the surface pCO 2 variations in the North Atlantic are mainly driven by the North Atlantic Oscillation. Also in the Southern Ocean, variability of the position and strength of the circumpolar front associated with the Southern Annular Mode (SAM) is thought to be responsible for the changes in water mass and biogeochemical dynamics, and hence CO 2 fluxes (Lenton and Matear, 2007;Lovenduski et al, 2007;Dufour et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the El-Nin˜o Southern Oscillation (ENSO) has been shown to influence the interannual variability of surface pCO 2 in the tropical Pacific . When averaged over periods longer than a few decades, the North Atlantic surface ocean pCO 2 has been shown to predominantly follow the evolution of atmospheric CO 2 (McKinley et al, 2011;Tjiputra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…SOCAT data products are used for model-to-data comparison, model evaluation and data assimilation in coupled and ocean-only biogeochemical models. Model-to-data comparisons of surface water f CO 2 have been carried out for seasonal (Tjiputra et al, 2012;Arruda et al, 2015) to multi-year timescales McKinley et al, 2016). In several studies, model data are subsampled to surface ocean pCO 2 observations from SOCAT Tjiputra et al, 2014;Turi et al, 2014).…”
Section: Scientific Applications Of Socatmentioning
confidence: 99%